La Loi sur les connaissements, les reçus et les cessions de biens en stock : quelques problèmes substantiels - Demers, Robert (Les Cahiers de droit, 1985)
The recent adoption of An Act respecting the transfer of property in stock has raised once again the controversy on the exact nature of the rights acquired by the holder of a bill of lading and a warehouse receipt. This problem is a familiar one for the specialist in banking law who well knows the endless contradictions concerning the interpretation of article 178 of the Bank Act. In this instance, the provincial legislature wished to give to quasi-banks (credit unions) the same possibility of securing loans as that afforded to banks under federal legislation. By a rather clever set of new rules added to the provincial Bills of Lading Act, this result is attained and is predicated on the idea that the creditor obtains full title of ownership on the goods ceded to him in the contract of loan. However, even in common law jurisdictions, the complete transfer of title is rarely admitted in such transactions and in codifying this dubious interpretation of case law, the legislature is perhaps not simplifying an already muddled area of our private law. Viewed in a historical perspective, Quebec law on this subject tends to reconcile the rights of the endorsee with those of civil law institutions, i.e. pledge. One hundred years of jurisprudence stands to that effect, until the '50s, where common law ideas seem to have taken hold of the courts. The result is of course a little bewildering and the student of our laws must gather together all of his patience in the study of this area already described early in the century by Mignault as being a Chinese brain-teaser.